Pengaruh Penggunaan Pembayaran Digital QRIS terhadap Kepuasan Pelanggan di Koperasi FKIP Universitas Mulawarman - Arnelita Dhewi Widheyawati; Sutrisno Sutrisno; Sudarman Sudarman; Indah Permatasari (Jurnal Ilmiah Wahana Pendidikan, 2026)
The shift from cash to non-cash transactions has accelerated in recent years, including at the FKIP Cooperative of Mulawarman University. The adoption of QRIS as a digital payment system offers greater convenience, faster transactions, and improved efficiency, which can enhance customers’ overall experience and satisfaction. This study examines whether the use of QRIS digital payments influences customer satisfaction. It aims to measure the extent to which QRIS usage affects customer satisfaction within the cooperative. This research employs a quantitative approach with a causal associative design. The population consists of cooperative customers, with a sample of 96 respondents selected for analysis. Data were collected through questionnaires and analyzed using classical assumption tests, simple linear regression, hypothesis testing (t-test), and the coefficient of determination, processed with SPSS.The findings reveal that QRIS digital payment usage has a positive and significant effect on customer satisfaction. This is evidenced by a regression coefficient of 0.638 and a t-value of 18.155 with a significance level of 0.000 (< 0.05). Accordingly, the alternative hypothesis (Ha) is accepted, indicating that QRIS usage significantly affects customer satisfaction, while the null hypothesis (H0) is rejected. Furthermore, the coefficient of determination (R Square) of 0.778 indicates that QRIS usage accounts for 77.8% of the variation in customer satisfaction, while the remaining 22.2% is explained by other factors beyond the scope of this study. Overall, these findings highlight the substantial role of QRIS in enhancing customer satisfaction at the FKIP Cooperative of Mulawarman University.